A Study of the Effect of the Difference in Energy Stored in Two Prosthetic Feet Made of Carbon Fiber Amputated Below the Knee on the Efficiency of Walking - Basim, Noor; Kahtan, Yassr Y. (Al-Nahrain Journal for Engineering Sciences, 2024)
ESAR feet are prosthetic feet with carbon fiber parts that store mechanical energy while standing and release it during propulsion. It is believed to reduce the metabolic energy needed for walking, and to promote the economy of walking. However, there is little scientific evidence to support this claim. This study aimed to compare the energy storage properties of two prosthetic feet made of carbon fiber using the P-Walk, G-Walk, and Podium devices developed for gait analysis, which is a systematic examination of human movement, enabling phasing, estimation of musculoskeletal performance, and determination of kinematic and motor parameters. The amount of energy was calculated for each of the feet using the load deflection test, and the results showed that the new artificial foot with an energy of 6.186 joules showed a great improvement in the results of the tests compared to the old artificial foot with an energy of 3.403 joules. The Podium device tests showed a significant improvement in walking patterns and pressure distribution after using a new foot. The pressure distribution became almost equal on both sides, and the angular deviation of COP decreased from -7 to 1.3 degrees. Ground reaction force vector tilt results also improved, with a body angle of 0 degrees and inclination varying slightly depending on the tibiofemoral angle for males. P-Walk results reveal left-sided static test pressure distribution, exposing amputees to osteoarthritis risk and revealing lack of confidence in prosthetic foot. After use the new prosthetic foot, amputees press more on right foot, indicating balance restoration. The G-Walk device shows the effectiveness of both healthy left and prosthetic foot when walking on an amputated right leg when use the new prosthetic foot. The amputated side's performance is similar to a healthy limb, with minimal difference and within normal limits. Walking cadence and speed values are within normal ranges, while stride length and step length are outside normal ranges for both sides. Obliquity results show a small difference in pelvic angles due to weak pelvic muscles, but these are close to standard values for prosthetic foot use. The amputee's opinions about the evaluation of the new prosthetic foot were good when using the T-score by 61.0 with a rate of 86.4%. It was a significant improvement compared to the old foot with an evaluation of 53.6 by 63.9%.